ANALYSIS OF MUFRODAD'S MANAGEMENT IN TRANSLATING THE LEXICAL OF THE SANTRI BOOK IN DARUSSALAM KARTASURA - Nodia Gustri Somahhida; Imam Makruf (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2022)
This article aims to analyze vocabulary mastery in translating lexical to determine students' vocabulary mastery in translating books. Arabic has a wealth of vocabulary so that the vocabulary is often different but the meaning is the same in Indonesian. In translating a book, a translator must master several elements related to Arabic translation. Errors in translating will have fatal consequences for the content of the text and others who understand it. This is the cause of the importance of mastering vocabulary in translating lexical books. The boarding house has its own unique method of learning. Translating lexical is one of its own characteristics in the dormitory. The research method used is descriptive qualitative, the object of research is the students of the Ula and Ulya levels which are the second and third levels of the 4 levels of learning at this Islamic boarding school. while the data collection techniques by observation, questionnaires and interviews. The results of the study showed that the mastery of vocabulary in translating lexical was assisted by the students' notes during the learning process. Students write translations of meaning into their respective books. So students can reopen when they forget. Memorization of vocabulary will make it easier in the future and can also increase vocabulary, but the frequency of finding the vocabulary when learning a student will indirectly memorize it by itself